Reduction in hypoxia‐reoxygenation‐induced myocardial mitochondrial damage with exogenous methane - Jász, Dávid Kurszán (J Cell Mol Med, 2021)
Albeit previous experiments suggest potential anti‐inflammatory effect of exogenous methane (CH(4)) in various organs, the mechanism of its bioactivity is not entirely understood. We aimed to investigate the potential mitochondrial effects and the underlying mechanisms of CH(4) in rat cardiomyocytes and mitochondria under simulated ischaemia/reperfusion (sI/R) conditions. Three‐day‐old cultured cardiomyocytes were treated with 2.2% CH(4)‐artificial air mixture during 2‐hour‐long reoxygenation following 4‐hour‐long anoxia (sI/R and sI/R + CH(4), n = 6‐6), with normoxic groups serving as controls (SH and SH + CH(4); n = 6‐6). Mitochondrial functions were investigated with high‐resolution respirometry, and mitochondrial membrane injury was detected by cytochrome c release and apoptotic characteristics by using TUNEL staining. CH(4) admixture had no effect on complex II (CII)‐linked respiration under normoxia but significantly decreased the complex I (CI)‐linked oxygen consumption. Nevertheless, addition of CH(4) in the sI/R + CH4 group significantly reduced the respiratory activity of CII in contrast to CI and the CH(4) treatment diminished mitochondrial H(2)O(2) production. Substrate‐induced changes to membrane potential were partially preserved by CH(4), and additionally, cytochrome c release and apoptosis of cardiomyocytes were reduced in the CH(4)‐treated group. In conclusion, the addition of CH(4) decreases mitochondrial ROS generation via blockade of electron transport at CI and reduces anoxia‐reoxygenation‐induced mitochondrial dysfunction and cardiomyocyte injury in vitro.